Pembentukan Karakter Percaya Diri Pada Pembelajaran Matematika Siswa SDUA Taman Harapan Curup : Verbal Reinforcement dan Non-Verbal Reinforcement - Syaripah Syaripah; Agil Ramadhan (AR-RIAYAH : Jurnal Pendidikan Dasar, 2022)
One of the advantages of character education in building students’ behavior is creating self-confidence. With character education, it is hoped that basic problems in the educational world, which have recently become a common concern, can be solved. Of course there are efforts from the school whether they are from the principal, teachers, and parents in overcoming it. One of the efforts is by using two types of reinforcement, namely verbal and non-verbal reinforcement. So the purpose of this research is to see how the use of reinforcement can create students' self-confident characters as well as the challenges faced by teachers to form self-confidence with verbal and non-verbal reinforcement. This study used a descriptive qualitative approach and the research subjects included the principal, teachers and students. Data collection techniques were observation, interviews and documentation. The data analysis technique used was data reduction, data display and conclusion drawing. The results showed that: (1) the teacher used verbal reinforcement such as giving comments, support, motivation and praise to students to create their self-confident characters, (2) the teacher also used non-verbal reinforcement such as giving smiles, approaching students, giving thumbs up and by giving gifts to form students’ confident character, (3) the challenges faced by teachers in using reinforcement are social jealousy, less conducive learning atmosphere and students behavior in class.